Saccadic Eye Movements in Depressed Elderly Patients - Carvalho, Nicolas (Public Library of Science, 2014)
The primary aim of this study was to characterize oculomotor performances in elderly depressed patients. The second aim was to investigate whether cognitive inhibition measured by the antisaccade task was associated with a psychomotor retardation or rather with a more specific cognitive-motor inhibition deficit. Twenty patients with a major depressive disorder and forty-seven healthy subjects performed two eye movement tasks. Saccadic reaction time and error rates were analyzed in the prosaccade task to obtain basic parameters of eye movements. Saccade latency, error rates and correction rates were evaluated in the antisaccade task to investigate inhibition capacities. Performances were impaired in patients, who exhibited a higher reaction time and error rates compared to controls. The higher time cost of inhibition suggested that the reaction time was not related to global psychomotor retardation alone. The higher time cost of inhibition could be explained by a specific alteration of inhibition processes evaluated by the antisaccade task. These changes were associated with the severity of depression. These findings provide a new perspective on cognitive inhibition in elderly depressed patients and could have important clinical implications for our understanding of critical behaviors involving deficits in inhibitory processes in the elderly.